El civil law frente al precedente judicial vinculante: diálogos con académicos de América Latina y Europa - Castro, Jordi Delgado; Díaz García, Luis Iván (Pontificia Universidad Católica del Perú, 2021)
This paper addresses binding judicial precedent. The semi- structured interview was used as a methodology for execution and a total of thirty-two academics, from ten countries in Latin America and Europe, participated of it. The results are structured around the arguments for and against precedent as a theoretical position; to narrate how vertex courts and inferior courts behave on precedents; and finally, to know the roadblocks that prevent following precedent correctly.

El presente trabajo aborda el tema del precedente judicial vinculante. Para su ejecución, se usó como metodología la entrevista semiestructurada, participando de ella un total de treinta y dos académicos de diez países de América Latina y Europa. Los resultados se estructuran en torno a los argumentos a favor y en contra del precedente como posición teórica; a narrar cómo se comportan los tribunales vértice y el resto frente a los precedentes; y, finalmente, a conocer los obstáculos que impiden seguir correctamente los precedentes.
Civil Law Versus Binding Judicial Precedent: Dialogues with Academics from (Latin) America and Europe
Keywords: Judicial precedent; Precedent application; Precedent in civil law; Precedent in common law; Precedente judicial; Seguimiento del precedente; Precedente en el derecho civil; Precedente en el common law; https://purl.org/pe-repo/ocde/ford#5.05.01